Resuscitative endovascular balloon occlusion of the aorta (REBOA) as adjunct treatment in life threatening postpartum hemorrhage: Fourteen years' experience from a single Norwegian center - Knut Haakon Stensæth; Marte Irene Skille Carlsen; Tone Shetelig Løvvik; Oddvar Uleberg; Jostein Rødseth Brede; Edmund Søvik (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Postpartum hemorrhage (PPH) remains a global health problem. The introduction of resuscitative endovascular balloon occlusion of the aorta (REBOA) in 2008 sought to enhance the management of hemorrhagic shock during PPH. In this study, we present a single Norwegian center's experience with REBOA as a supportive treatment in combating life threatening PPH. Material and methods This is a historical cohort study from St Olav's University Hospital, with data from period 2008–2021. It includes all patients who underwent REBOA as an adjunct treatment due to life threatening PPH, analyzing the outcomes and trends over a 14‐year period. Results A total of 37 patients received REBOA as an adjunct treatment. All procedures were technically successful, achieving hemodynamic stability with an immediate average increase in systolic blood pressure of 36 ± 22 mmHg upon initial balloon inflation. Additionally, a downward trend was noted in the frequency of hysterectomies and the volume of blood transfusions required over time. No thromboembolic complications were observed. Conclusions Our 14 years of experience at St Olav's Hospital suggests that REBOA serves as a safe and effective adjunct interventional technique for managing life‐threatening PPH. Furthermore, the findings indicate that incorporating a multidisciplinary approach to enable rapid aortic occlusion can potentially reduce the necessity for blood transfusions and hysterectomies.